Centralization and integration of public health systems: Perspectives of public health leaders on factors facilitating and impeding COVID-19 responses in three Canadian provinces. (January 2023) - Smith, Robert William; Jarvis, Tamika; Sandhu, Harman Singh; Pinto, Andrew D.; O'Neill, Meghan; Di Ruggiero, Erica; Pawa, Jasmine; Rosella, Laura; Allin, Sara
Highlights: Effective and equitable pandemic responses require well structured public health (PH) systems. Provincial PH systems in Canada vary by degrees of centralization and integration. Centralization and integration may facilitate rapid mobilization and coordination of province-wide responses. Decentralization may facilitate timely and coordinated local responses where limited provincial guidance. Cross-cutting challenges across provinces related to government transparency, investments, and mandate ambiguity. Abstract: The extent to which power, resources, and responsibilities for public health are centralized or decentralized within a jurisdiction and how public health functions are integrated or coordinated with health care services may shape pandemic responses. However, little is known about the impacts of centralization and integration on public health system responses to the COVID-19 pandemic. We examine how public health leaders perceive centralization and integration facilitated and impeded effective COVID-19 responses in three Canadian provinces. We conducted a comparative case study involving semi-structured interviews with 58 public health system leaders in three Canadian provinces with varying degrees of centralization and integration. Greater public health system centralization and integration was seen by public health leaders to facilitate more rapidly initiated and well-coordinated provincial COVID-19 responses. Decentralization may have enabled locally tailored responses in the context of limited provincial leadership. Opacity in provincial decision-making processes, jurisdictional ambiguity impacting Indigenous communities, and ineffectual public health investments were impediments across jurisdictions and thus appear to be less impacted by centralization and integration. Our study generates novel insights about potential structural facilitators and impediments of effective COVID-19 pandemic responses during the second year of the pandemic. Findings highlight key areas for future research to inform system design that support leaders to manage large-scale public health emergencies.